Use of MRI to predict symptomatic haemorrhagic transformation after thrombolysis for cerebral ischaemia. Issue 4 (3rd February 2020) - Caparros, François; Kuchcinski, Gregory; Drelon, Agathe; Casolla, Barbara; Moulin, Solene; Dequatre-Ponchelle, Nelly; Henon, Hilde; Cordonnier, Charlotte; Pruvo, Jean-Pierre; Leys, Didier
Abstract : Background and objective: Predictors of symptomatic haemorrhagic transformation (s-HT) of cerebral ischaemia after intravenous recombinant tissue-plasminogen activator (rt-PA) were identified in studies using CT scans. We evaluated whether MRI can identify other predictors. Method: We analysed predictors of s-HT in a cohort of consecutive patients who received intravenous rt-PA for cerebral ischaemia after MRI at baseline. We used receiver operating characteristic curves considering an area under the curve (AUC) of 0.70 or higher as indicating acceptable discrimination. Results: Of 944 patients, 49 patients (5.2%) developed s-HT. Clinical factors independently associated with s-HT were age (adjusted OR (adjOR) 1.03 for 1 year increase; 95% CI 1.01 to 1.05), excessive alcohol consumption (adjOR 3.13; 95% CI 1.32 to 7.42), recent transient ischaemic attack (adjOR 2.88; 95% CI 1.04 to 7.95) and baseline national institutes of health stroke scale score (adjOR 1.06 for 1 point increase; 95% CI 1.02 to 1.10). MRI predictors were vascular hyperintensities (adjOR 3.89; 95% CI 1.50 to 10.08), old infarcts (adjOR 2.01; 95% CI 1.11 to 3.66) and volume of diffusion-weighted imaging (DWI) abnormality (adjOR 1.02 for 1 cm 3 increase; 95% CI 1.01 to 1.03). The only variable with an acceptable discrimination was volume of DWI abnormality (AUC 0.72; 95% CI 0.64 to 0.79), a value of 4 cm 3 predicting s-HT with a 78% sensitivity and 58% specificity. Variables that can be assessed only with MRI did not predict s-HT. Conclusion: Although the volume of DWI abnormality predicts s-HT, other imaging characteristics that can only be assessed with MRI were not significantly associated with s-HT. Trial registration number NCT01614080